Parenting Style and Adolescent Mental Health: The Chain Mediating Effects of Self-Esteem and Psychological Inflexibility - Peng, Biao; Hu, Ningning; Yu, Huiying; Xiao, Hanshi; Luo, Jie (Frontiers in Psychology, 2021)
Based on interpersonal acceptance-rejection theory, family systems theory, and psychological inflexibility theory, this study aimed to examine the mediating roles of a protective factor (self-esteem) and a risk factor (psychological inflexibility) on the influence of parenting style on adolescent mental health. A sample of Chinese adolescents (n = 916, 46% male, mean age = 14.44 years, SD = 1.84 years) completed the Short Egna Minnen Barndoms Uppfostran, the Rosenberg Self-esteem Scale, the Avoidance and Fusion Questionnaire for Youth, the Satisfaction with Life Scale, and the Depression Subscale of the Youth Self-Report. Results show that the self-esteem and psychological inflexibility play a chain mediating role in the relationship between parenting style and adolescent mental health. Specifically, parental emotional warmth had a positive effect on adolescent mental health through the chain mediating effects of self-esteem and psychological inflexibility. Parental rejection and parental over-protection had negative effects on adolescent mental health by lowering self-esteem but increasing psychological inflexibility. These results provide further guidance in the prevention of and intervention in adolescent mental health problems.